2008
DOI: 10.3198/jpr2008.02.0080crg
|View full text |Cite
|
Sign up to set email alerts
|

Registration of RMUP‐C5, a Random Mated Population of Upland Cotton Germplasm

Abstract: RMUP‐C5 (Random Mated Upland Population Cycle 5) (Reg. No. GP‐893, PI 652942) is a unique random mated germplasm population of Upland cotton (Gossypium hirsutum L.) involving six cycles of random mating beginning with an 11 parent half diallel. This germplasm was developed through cooperative research by the USDA‐ARS, Mississippi Agricultural and Forestry Experiment Station, North Carolina State Agricultural Experiment Station, and Cotton Incorporated. Parents used in development represented nonrelated or dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…1 and Additional file 2) [9]. The effectiveness of random-mating and its consequence on structure of this population was evaluated using 6039 SNP and 223 SSR markers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 and Additional file 2) [9]. The effectiveness of random-mating and its consequence on structure of this population was evaluated using 6039 SNP and 223 SSR markers.…”
Section: Resultsmentioning
confidence: 99%
“…1. The details of the population development were previously described by [4, 9, 27]. In brief, a half-diallel crossing scheme between 11 parents were followed to produce 55 F 1 in 2002.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Random mating procedures have provided an important methodology to break undesirable associations and to form new combinations in several crop plants, including tobacco [9], sorghum [10], soybean [11], and oats [12]. Random mating has previously been shown to reduce correlations between traits in cotton as well [8, 1315]. Random mating requires a considerable expenditure of time and energy.…”
Section: Introductionmentioning
confidence: 99%
“…These results are at odds with results from studies of agronomically elite germplasm that often report negative relationships between yield components and fiber quality. Prior studies by Jenkins et al (2008) also reported changes in correlations among traits after six cycles of random mating in a cotton population. The process of random mating, whether using bulked pollen (Jenkins et al, 2008) or male‐sterile methodology, may change genetic relationships by reconfiguring epistatic interactions.…”
Section: Characteristicsmentioning
confidence: 87%